Dissecting the osmotic and oxidative stress responses in salt-tolerant and salt-sensitive wheat genotypes under saline conditions - Ulkar Ibrahimova; Javanshir Talai; Md. Mahadi Hasan; Irada Huseynova; Vaseem Raja; Anshu Rastogi; Hamideh Ghaffari; Marek Zivcak; Xinghong Yang; Marian Brestic (Plant, Soil and Environment)
Salinity represents a significant abiotic stress that markedly influences plant growth through osmotic stress induction. Plants commonly undergo osmotic adaptation when subjected to prolonged periods of saline stress. The current experiments were conducted on five wheat (Triticum aestivum L.) genotypes with contrasting salt tolerance capacities - Mirbashir 128, Gobustan, Gyzyl bughda, Fatima, and Zirva 80 under salinity stress caused by 150 mmol NaCl. The relative water content and osmotic potential were found to decrease significantly in salinity-sensitive genotypes (Fatima and Zirva 80) compared to salinity-tolerant ones (Mirbashir 128, Gobustan, and Gyzyl bughda) when treated with 150 mmol NaCl. Salinity also caused the accumulation of soluble sugars and proline, the amounts of which were observed to be higher in salinity-tolerant genotypes than sensitive ones, while lipid peroxidation was higher in salinity-sensitive genotypes. In salinity-tolerant genotypes, 150 mmol NaCl caused increased antioxidant enzyme activities and accumulation of flavonoids, including anthocyanins, confirming the rapid development of the stress reactions in these plants. Differences in the osmoregulation indicators and antioxidant responses between salinity-tolerant and sensitive plants are assumed to be related to their salinity-tolerance traits. This investigation provides pivotal foundational insights for enhancing the salt tolerance of wheat genotypes, thereby potentially enhancing both yield and quality in diverse wheat cultivars thriving in saline environments.